2020
DOI: 10.1089/jayao.2019.0153
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Illness Perceptions in Thyroid Cancer Survivors: Does Age Matter?

Abstract: Purpose: To examine the role of differentiated thyroid cancer (DTC) patients' age in illness perceptions and psychological distress, and the potential moderating role of age in the relationship between illness perceptions and psychological distress. Methods: We used the Netherlands Cancer Registry to select all patients diagnosed with thyroid cancer between 1990 and 2008 (n = 568). Patients filled out the Hospital Anxiety and Depression Scale (HADS) and Brief Illness Perception Questionnaire. Levels of psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…The association between patients’ perceptions and anxiety, depression, or QoL in TC has been reported in 16 studies [ 17 , 34 - 36 , 40 , 43 , 44 , 46 , 71 - 78 ]. Patients’ worries over recurrence were linked to impaired QoL [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between patients’ perceptions and anxiety, depression, or QoL in TC has been reported in 16 studies [ 17 , 34 - 36 , 40 , 43 , 44 , 46 , 71 - 78 ]. Patients’ worries over recurrence were linked to impaired QoL [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 76 ] found that fear of recurrence and fear of exhausting effective treatment options in the future were related to increased anxiety levels. In addition, several studies [ 36 , 44 , 77 ] showed that perceived stress, or having more negative perceptions of cancer, was associated with lower QoL. Kurumety et al .…”
Section: Resultsmentioning
confidence: 99%
“…Patients treated for TC have been previously shown to have dissatisfaction and unmet information and psychological needs with their initial workup and treatment for their cancer. 18,20,36,40,41 Our approach, enabling survivors to articulate their experiences through free-text response, elucidated the salient aspects of their experience that made them respond as they did to the closed items. A key finding of this study is that misunderstanding and unmet expectations resulted when patients were unaware that subsequent treatment options would be informed by the results of preceding steps.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated for TC have been previously shown to have dissatisfaction and unmet information and psychological needs with their initial workup and treatment for their cancer . Our approach, enabling survivors to articulate their experiences through free-text response, elucidated the salient aspects of their experience that made them respond as they did to the closed items.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated thyroid cancer (DTC), arising from thyroid follicular cells that include both papillary and follicular types, is the most common endocrine malignancy with increasing incidence rates. 1 , 2 The thyroid gland, consisting of two connected lobes, is one of the largest endocrine glands in the human body, weighing 20–30 g in adults. Thyroid lesions are often found on the gland, with a prevalence of 4–7%.…”
Section: Introductionmentioning
confidence: 99%